(untitled) (Italian Journal of Public Health, 2005)
Health Technology Assessment (HTA) is a process used to evaluate the clinical effectiveness and costeffectiveness of health technologies by a systematic review of clinical, economic, and utilization research. Despite widespread investment in patient safety technologies in the U.K., U.S., and elsewhere, little HTA has been done to establish the clinical or cost-effectiveness of these technologies. The HTA and patient safety literature suggests there are four categories of patient safety HTA, including HTA for existing safety technologies, underutilized safety technologies, emerging safety technologies, as well as safety aspects of technologies with a non-safety primary purpose. Recent HTA and other research, including a 2002 evidencebased evaluation of patient safety technologies from the U.S. Agency for Health Research and Quality, provide an important foundation for a more comprehensive approach to patient safety HTA. However, HTA programs must address prioritization, methodology, and dissemination challenges introduced by patient safety technologies before significant progress can Te made.